0VIP0SITION PREFERENCE OF SCJRPOPHAGA INCERTULAS (WALKER) ON DIFFERENT VARIETIES OF RICE UNDER CAGED CONDITION - Shahjahan, Md (Biological Sciences - PJSIR, 2002)
Preference of Yellow Stem Borer (YSB) female for egg deposition on 21 aus and 11 arnan rice varieties were observed under caged conditions during 1992, 1993 and 1994. Significant differences in the number of egg mass deposition on different rice va1ieties were found excepti ng on aus, 1992 and aman, 1994. The dorsal side ofleaf was preferred to ventral side for egg deposition irrespective of the rice variety . Again , the middle portion of leaf was preferred for egg laying to basal and apical portions in all the varieties . Length and width of egg masses deposited on different rice varieties did not differ significantly except the length of the egg mass in aus season. The number of egg masses deposited by the female YSB was positively correlated with leaf blade colour but negatively correlated with plant height, 2nd leaf length and width , number of leaves, number of tillers and leaf hair in both aus and aman rice. So, the leaf blade colour induces egg deposition , while other plant characters reduce it.